Animated Concept Cartoons as a Starter for Cognitive Conflict in Online Science Learning: A Case of Circular Motion - Ertugrul Ozdemir (Universitas Pendidikan Indonesia, 2022)
Before taking formal science education, learners usually construct preconceptions based on their daily life experiences, many of which are scientifically unacceptable misconceptions. In formal science learning, new concepts often contradict these misconceptions. To correct a misconception, it is first needed to create dissatisfaction about it by initiating cognitive conflict. This study aims to create an animated concept cartoon about circular motion and evaluate its usability to start cognitive conflict about centrifugal force misconception in online learning. This is a one-group quasi-experimental study whose participants are 110 undergraduate students with non-science backgrounds. An animated concept cartoon about circular motion and an online data collection instrument were developed and implemented for the participants. Results showed that half of the participants might be considered to be in a status of cognitive conflict after reading the animated concept cartoon. In addition, participants' overall satisfaction with the animated concept cartoon was found to be relatively high. Participants' satisfaction with the animated concept cartoon was equal for students with and without cognitive conflict. In the context of these findings, the animated concept cartoon may be considered an enjoyable and useful learning activity to initiate cognitive conflict in online science learning.